Efforts to Improve the Ability to Recognize Letters in Children Aged 4-5 Years with Movable Alphabet Montessori Media - Alya Maharani; Dwi Suryani, Yuni (Yayasan Corolla Education Centre, 2025)
This study aims to improve the letter recognition ability of children aged 4–5 years using the Movable Alphabet Montessori media at TK IT Al-Hafiz Cendekia. Employing a Classroom Action Research (CAR) design, the study followed the Kemmis and McTaggart model consisting of planning, action, observation, and reflection phases. The research subjects were 20 children (10 boys and 10 girls) selected through purposive sampling based on their age group and observed challenges in letter recognition. Data collection was conducted through structured observation and documentation of classroom activities. The indicators used in observations included fine motor coordination (hand-eye coordination, finger dexterity, and muscle control), letter identification accuracy, and student engagement during activities. Data analysis was carried out using both quantitative methods—calculating the percentage of students meeting learning criteria—and qualitative methods—analyzing field notes and documentation for insights into learning behavior. In Cycle I, only 20% of children reached the target criteria. However, Cycle II showed improvement with 75% achieving the desired outcomes. These findings demonstrate that the Movable Alphabet media effectively enhances early literacy development through hands-on, child-centered learning experiences.